The Dynamics of Online Gaming in the Learning Lives of Muslim Students: A Qualitative Study - Juliwis Kardi; Taufik Hidayat; Adi Putra; Iswandi Iswandi; Sulasmi Sulasmi (Pascasarjana Universitas KH. Abdul Chalim, 2026)
Online games have become a necessity in modern society, especially among teenagers and adults. While they are primarily for entertainment and social interaction, they also impact the learning process. Online games have grown rapidly recently, especially in the world of e-sports. There are many variations or types of online games, such as PUBG, Domino Island, Free Fire, Poker, and other online games, which create engaging gameplay. The more engaging the game, the more people play it. Online games have become a new lifestyle for students and adults. The presence of online games has significantly eroded students' motivation to learn at school, resulting in a decline in the quality of learning. This study, however, is a crucial activity in the education system. This study aims to analyze the impact of online games on high schools. This study uses a survey method using quantitative research methods. This type of research uses a survey because in data collection, the author gathered information from respondents using a questionnaire as the primary method. Overall, the research findings show that in State Islamic Senior High Schools throughout West Pasaman, the impact of Mobile Legends on student achievement is a major concern, as measured by frequency and percentage calculations. The researcher found a 72% impact of the Mobile Legend game on students. Meanwhile, the decline in student learning achievement, according to the distributed questionnaire, reached 63%. Several activities that should be created to avoid the impact of Mobile Legends are extracurricular activities and homework, as well as strict supervision of students' smartphones. It is important to maintain balance in the approach taken by State Islamic Senior High Schools in West Pasaman.